Penerapan Analisis Untuk Segmentasi Pasar Produk Gutme Terhadap Tingkat Penjualan Produk UMKM - Dyahnesa Harul Puspitaningrum; Hwihanus (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The aim of this research is to use market segmentation analysis to increase sales of GUTME products to micro, small and medium enterprises (MSMEs). Although GUTME products have great potential, they face problems getting the right customers because they do not understand the market characteristics and different consumer preferences. Therefore, a proper understanding of market segmentation is needed to create better marketing strategies. Statistical methods that use quantitative analysis and data-based market segmentation are used in this research. Data was collected through a survey conducted on 500 customers who are the target market for GUTME products. The aim of the survey is to identify customer demographics, psychographics and buying behavior.